-20+18t=-(6t-4)

Simple and best practice solution for -20+18t=-(6t-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20+18t=-(6t-4) equation:


Simplifying
-20 + 18t = -1(6t + -4)

Reorder the terms:
-20 + 18t = -1(-4 + 6t)
-20 + 18t = (-4 * -1 + 6t * -1)
-20 + 18t = (4 + -6t)

Solving
-20 + 18t = 4 + -6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '6t' to each side of the equation.
-20 + 18t + 6t = 4 + -6t + 6t

Combine like terms: 18t + 6t = 24t
-20 + 24t = 4 + -6t + 6t

Combine like terms: -6t + 6t = 0
-20 + 24t = 4 + 0
-20 + 24t = 4

Add '20' to each side of the equation.
-20 + 20 + 24t = 4 + 20

Combine like terms: -20 + 20 = 0
0 + 24t = 4 + 20
24t = 4 + 20

Combine like terms: 4 + 20 = 24
24t = 24

Divide each side by '24'.
t = 1

Simplifying
t = 1

See similar equations:

| 5x+7z=2+7y | | 5sinx+7cosx=2 | | V(x)=x(5-2x)(10-2x) | | 7sinx+7cosx^2=7 | | 2g+5=1g-4 | | a^2+b^2=40000 | | 2(x+5)(x-2)=x(x+5)+90 | | -6x^2-3x-3=0 | | 3x-8=2+4x-8 | | 7x-3(c+6)=14 | | 26x+4=18 | | 2x=80-2x | | 0.36/8 | | 10n^2-29n-44=0 | | 445-6x=0 | | -34z=14 | | -((2x)/(x-1)^3)=0 | | 4x^2-49x-900=0 | | 4x-9-6x=2(x+5)-3 | | 0.5x+0.3=.2 | | -5x-12y=15 | | 6*6/2(3)=4 | | -0.5(x-2)=-x-2 | | 2(x-16)=0 | | -((20x)/sqrt(9-20x^2)=2 | | y/8-x/4=1 | | 13x-1=116 | | y=2x^2+(4)x-7 | | -((20x)/(9-20x^2)^(1/2))=2 | | 2x+(3x)=25 | | 4(2-6x)=6(2-4x) | | 18=7p+p^2 |

Equations solver categories